A new algorithm is employed for the efficient allocation of distributed generation resources - Kumar, Elipilli Anil; Mudavath, Gopichand Naik; Narasimhulu, Tamminana (Institute of Advanced Engineering and Science, 2024)
The bat algorithm (BA) has emerged as a promising meta-heuristic approach, demonstrating its efficiency in tackling diverse optimization problems across the areas such as engineering design, issues with economic load dispatch, power and energy systems, image processing, and medicinal applications. Due to its potential to increase grid resilience, decrease greenhouse gas emissions, and increase energy efficiency, the incorporation of distributed generation (DG) into contemporary power systems has drawn a lot of interest. This paper presents technique for the optimal allocation of DG units, aiming to address existing challenges and improve the overall performance of the power system. The proposed BA technique combines advanced optimization algorithms with comprehensive power system modelling to identify the optimal locations and capacities for DG installation. Key factors are taken into account to formulate a multi-objective optimization problem that includes minimizing power losses, enhancing voltage stability, and minimizing the environmental impact while considering economic feasibility. The algorithm is applied on standard IEEE 33 and 69 bus systems as test cases and a result has been discussed.